Clinical and epidemiological aspects of streptococcus pyogenes pharyngitis and carriage in Africa - Engel, Mark E.; Mayosi, Bongani M. (SA Heart Journal, 2017)
Infection with Group A β-haemolytic Streptococcus, also known as Streptococcus pyogenes, results in various mucosal and skin diseases including pharyngitis. An exaggerated immune response to a single or repeated group A streptococcal (GAS) infection subsequently results in acute rheumatic fever (ARF) and, in the absence of intervention, repeated bouts of ARF may in turn result in progression to RHD, particularly in those ARF patients with cardiac involvement. Addressing GAS pharyngitis through appropriate primary prevention measures and treating all symptomatic GAS sore throats with a course of oral or parenteral penicillin presents an opportunity for the primary intervention of RHD. Failure to eradicate streptococci from the pharynx occurs in about one third of non-treated cases, giving rise to carrier status in those individuals harbouring intracellular GAS and thus representing a potential source of the acquisition of infections for other children and adults. Improved living conditions and access to healthcare during the last century are credited for the considerable decline in the prevalence of ARF and RHD in developed countries. However, a few studies have been reported from within Africa, and in these GAS carriage ranged around 9.0%. In South African studies GAS carriage isolation rates, which range from 1.62% to16.8%, were reported. As regards the prevalence of GAS pharyngitis, it is generally higher in developing countries and impoverished communities within industrialised nations. The most-up-to-date data from South Africa was collected more than 30 years ago with rates then ranging from 23.2% to 45.5%. There are no incidence data on GAS pharyngitis in Africa. This review found that there is a need to document the epidemiology of GAS carriage and GAS pharyngitis in school children of all ages within Africa. Molecular characterisation of strains harboured in the pharynx of carriers and of those isolated during bouts of pharyngitis, will help to identify risk factors associated with carriage in school-aged children and infl uence the planning and evaluation of management programmes in the screening of pharyngeal carriers and treatment of GAS pharyngitis.